2022
DOI: 10.1111/mec.16654
|View full text |Cite
|
Sign up to set email alerts
|

Cophylogeny and specificity between cryptic coral species (Pocillopora spp.) at Mo′orea and their symbionts (Symbiodiniaceae)

Abstract: The congruence between phylogenies of tightly associated groups of organisms (cophylogeny) reflects evolutionary links between ecologically important interactions. However, despite being a classic example of an obligate symbiosis, tests of cophylogeny between scleractinian corals and their photosynthetic algal symbionts have been hampered in the past because both corals and algae contain genetically unresolved and morphologically cryptic species. Here, we studied co‐occurring, cryptic Pocillopora species from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 121 publications
8
49
0
Order By: Relevance
“…represent an assemblage of cryptic species with differential bleaching susceptibility [ 35 ]. In Pocillopora spp., we have shown that morphological taxonomy [ 36 ] is a poor indicator of species identity [ 35 , 37 ], and therefore, it is possible that both of our trials contained more than one species. Since at least some of the species in this complex are physiologically unequal as demonstrated by contrasting bleaching susceptibility [ 35 ], it is also possible that they differentially translate colony integration into emergent aspects of colony performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…represent an assemblage of cryptic species with differential bleaching susceptibility [ 35 ]. In Pocillopora spp., we have shown that morphological taxonomy [ 36 ] is a poor indicator of species identity [ 35 , 37 ], and therefore, it is possible that both of our trials contained more than one species. Since at least some of the species in this complex are physiologically unequal as demonstrated by contrasting bleaching susceptibility [ 35 ], it is also possible that they differentially translate colony integration into emergent aspects of colony performance.…”
Section: Discussionmentioning
confidence: 99%
“…Trials were conducted in 150 l tanks that were heated, mixed, chilled, illuminated and supplied with CO 2 gas. We targeted P. verrucosa for collection based on morphology [ 36 ], although we probably worked with cryptic species [ 35 , 37 ] and, hereafter, we refer to our study organism as Pocillopora spp. Sampled corals were used to prepare single branches (nubbins), ‘artificial colonies’ (aggregates) of nubbins from the same genotype that are glued to a plastic base in an array creating the branch spacing of natural colonies (but lacking integration because the nubbins are not connected by tissue or skeleton) and intact colonies (colonies).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, P. verrucosa typically hosts Cladocopium sp. across the Pacific Ocean at large, not Symbiodinium , which may provide further evidence to the argument that Pocillopora ‐ Symbiodinium associations represent an adaptation to warmer and nutrient‐rich waters (Johnston et al, 2022; Turnham et al, 2021). Although the Red Sea P. verrucosa Cladocopium C1 has been portrayed as a high‐performance microalgal partner (Sawall et al, 2014, 2015), its association might be constrained to narrow environmental regimes.…”
Section: Discussionmentioning
confidence: 70%
“…However, there remains a knowledge gap concerning where and why particular Symbiodiniaceae taxa are associated with particular coral genera. To date, coral studies have typically focused on the factors structuring these symbioses in either a single geographical location (Johnston, Cunning, & Burgess, 2022;O'Brien et al, 2020;Osman et al, 2020;Pollock et al, 2018;Ricci et al, 2022) or for a single Symbiodiniaceae genus at the regional level (Turnham et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, there remains a knowledge gap concerning where and why particular Symbiodiniaceae taxa are associated with particular coral genera. To date, coral studies have typically focused on the factors structuring these symbioses in either a single geographical location (Johnston, Cunning, & Burgess, 2022; O'Brien et al, 2020; Osman et al, 2020; Pollock et al, 2018; Ricci et al, 2022) or for a single Symbiodiniaceae genus at the regional level (Turnham et al, 2021). It is important to consider how environmental and geographical factors together are driving the establishment and maintenance of this symbiotic relationship, as the diversity, distribution and stability of Symbiodiniaceae communities is central to coral's future in an increasingly warmer, high CO 2 world.…”
Section: Introductionmentioning
confidence: 99%